Are HIV-positive young black MSM having safer sex than those who are HIV-negative?. (April 2017) - Crosby, Richard A; Mena, Leandro; Geter, Angelica
In the United States, young Black men who have sex with men (YBMSM) bear the single largest burden of the HIV/AIDS epidemic. Whether HIV-positive men in this population practice relatively safer sex than their HIV negative counterparts has not been recently investigated. The purpose of this study was to compare selected sexual risk behaviors between YBMSM who are HIV-positive to their HIV-negative counterparts of the same geographic location in the southern US. A convenience sample of 600 YBMSM completed a computer-assisted self-interview in a private area of a clinic dedicated to sexual health. Frequency/prevalence of 16 sexual risk behaviors was compared between men who were HIV-positive and those who were HIV-negative at the time. Bivariate associations were tested in regression models adjusted for age and having a main male sex partner. One-quarter of the sample (25.5%) was HIV-positive at study enrollment. Remarkably few differences in sexual risk behaviors were observed. HIV-positive men were less likely to report recent sex with a woman ( P  = .003), and they were more likely to report recent sex with persons known to be HIV-positive ( P  < .001). Of 16 assessed outcome measures, these two significant findings represented the only significant differences in the adjusted analyses. YBMSM residing in the southern US may experience high levels of HIV exposure risk or risk of exposing others to HIV. A particularly urgent need exists to improve post-diagnostic HIV prevention efforts for HIV-positive YBMSM.